Electrolyte and Interphase Design for Magnesium Anode: Major Challenges and Perspectives. Issue 43 (22nd March 2022) - Sun, Yue; Ai, Fei; Lu, Yi‐Chun
Abstract: The rechargeable magnesium battery (RMB) is regarded as a high‐energy, safe, and cost‐effective alternative for conventional batteries. Unfortunately, the passivation and uneven Mg growth not only raise the voltage hysteresis but also shorten the cycle life of RMBs. In this review, Mg passivation induced by electrolytes/contaminants, growth patterns of high dimensional Mg 0, and mechanisms of Mg anode degradation are discussed. The recent efforts on suppressing electrolyte decomposition and uneven Mg growth including electrolyte/interphase modifications through additives, weakly coordinating anions, artificial interphases, and 3D magnesiophilic hosts are summarized. Finally, the future directions in stabilizing Mg anode and realizing high‐performance RMBs are highlighted. Abstract : In this review, the degradation mechanism of Mg anode and strategies to overcome the passivation/dendrite issue are discussed. Recent progresses including electrolyte modifications through additives, weakly coordinating anions design, construction of artificial interphases and 3D magnesiophilic hosts are summarized, and future directions in realizing advanced RMBs are discussed.